Fake Instagram: Manajemen Identitas Dan Privasi Melalui Fenomena Finstagram - Desideria, Nathania; Syaki, Wifka Rahma (Tuturlogi: Journal of Southeast Asian Communication, 2022)
With the surge in Instagram's popularity among Indonesian college students, a notable trend emerges where many manage a secondary account, commonly referred to as Finstagram (Fake Instagram). This distinct account serves as an outlet for them to candidly share stories from their daily lives, often with a more select audience. Recognizing the significance of this phenomenon, this research embarked on an exploration to fathom the depth of their privacy management on Finstagram. By harnessing the Communication Privacy Management theory, the study intended to dissect the underlying motivations and mechanisms that govern students' decisions on their digital privacy. Utilizing a qualitative methodology anchored in a phenomenological approach and a constructivist paradigm, the research delved into the lived experiences of these students. Data, rich in narratives, was gathered from meticulous in-depth interviews. Preliminary findings unveiled several pivotal privacy strategies. Students frequently adopted pseudonyms, consciously refrained from showcasing their faces in profile pictures, and judiciously harnessed the private account feature on Instagram. Interestingly, while they reserved highly personal information for a tight-knit circle labeled "close friends", instances of boundary turbulence were scarcely reported. Yet, the tug-of-war in privacy management, denoted as dialectics, was consistently evident.